1996
DOI: 10.1002/(sici)1096-8628(19961002)65:1<56::aid-ajmg9>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion 5p accompanied by dicentric ring formation of the deleted segment resulting in trisomy 5p13‐cen

Abstract: Karyotypes with an interstitial deletion and a marker chromosome formed from the deleted segment are rare. We identified such a rearrangement in a newborn infant, who presented with macrocephaly, asymmetric square skull, minor facial anomalies, omphalocele, inguinal hernias, hypospadias, and club feet. The karyotype 46,XY,del(5) (pter --> p13::cen --> qter)/47,XY,+dicr(5)(:p13 --> cen::p13 --> cen), del(5)(pter --> p13::cen --> qter) was identified by banding studies and FISH analysis in the peripheral lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…At least 11 additional cases of deletion associated with a complementary ring chromosome have been reported in the literature. 31,[48][49][50][51][52][53][54][55][56][57] These cases all involved visible deletions in one homolog, whereas case 7 in this study is the first reported cryptic deletion associated with ring-chromosome formation. Three of the previously reported cases 31,55,57 involve the more rare class of marker chromosomes that do not contain detectable alpha-satellite sequences and are referred to as neocentric markers.…”
Section: Rediscovery Of the Mcclintock Mechanism Of Small-ring Formatmentioning
confidence: 99%
“…At least 11 additional cases of deletion associated with a complementary ring chromosome have been reported in the literature. 31,[48][49][50][51][52][53][54][55][56][57] These cases all involved visible deletions in one homolog, whereas case 7 in this study is the first reported cryptic deletion associated with ring-chromosome formation. Three of the previously reported cases 31,55,57 involve the more rare class of marker chromosomes that do not contain detectable alpha-satellite sequences and are referred to as neocentric markers.…”
Section: Rediscovery Of the Mcclintock Mechanism Of Small-ring Formatmentioning
confidence: 99%
“…In the literature, there are some mosaic cases of clones with a deletion and an additional ring separately [Gutiérrez‐Angulo et al, 2002; Gereltzul et al, 2008; Kara et al, 2008], but such cases are extremely rare. In newborn infants, only one other case has been reported [Schuffenhauer et al, 1996] with a deletion and a ring of chromosome 5; this baby showed a mosaicism of 46,XY,del(5)/47,XY, del(5),+dic(5), with macrocephaly, asymmetric square skull, minor facial anomalies, omphalocele, inguinal hernias, hypospadias, and club feet. The break points of the deletion shared cen and p13 with those of the dicentric ring chromosome; this case had partial duplication of 5p (p13 → cen), and the mechanisms of del(5) and dic(5) were relatively straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…The most common aneuploidies associated with omphalocele are trisomy 18 and 13, Turner syndrome (45, X), and triploidy. Various other chromosomal abnormalities have been found in newborns and fetuses with omphalocele, including rearrangements of 1q (19, 20), 5p (21, 22), partial trisomy 6q (23), and in Miller–Dieker syndrome (MIM #247200) due to 17p deletion (24–26). Here, we present the case of an 11‐month‐old boy with omphalocele who has a duplication of 3q27.3‐qter due to the malsegregation of a maternal t(3;4)(q27.3;q32.3) but does not show the BDLS or dup3q phenotype.…”
Section: Reported Patients With Dup3qmentioning
confidence: 99%